S. FERNE: LABOR PRINCIPLE AND MODERN REFORM SCHOOLS (Pedagogy of Higher and Secondary Education, 2008)
In the article paid a regard to labour principle of education of S. Frene. Recommendations are expressed in relation to the use of him at modern Ukrainian school.